2016
DOI: 10.5942/jawwa.2016.108.0157
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection Data Integrity in Washington State

Abstract: Disinfection data inaccuracies found in Washington State water systems reveal opportunities for improving data collection and disinfection practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Typical drivers for accurate metering, including accounting (e.g., billing) or critical chemical pacing (e.g., ammonia for chloramination), may not apply to many reactors. A recent study of 33 systems in the state of Washington found that 58% did not directly measure flows for disinfection calculations (Deem & Feagin ); 85% of systems also did not calibrate or verify the peak hourly flow or the plant effluent flowmeter. A reactor in which influent flow exceeds effluent flow (i.e., volume accumulation in a reactor used for both storage and disinfection) could also produce V norm > 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical drivers for accurate metering, including accounting (e.g., billing) or critical chemical pacing (e.g., ammonia for chloramination), may not apply to many reactors. A recent study of 33 systems in the state of Washington found that 58% did not directly measure flows for disinfection calculations (Deem & Feagin ); 85% of systems also did not calibrate or verify the peak hourly flow or the plant effluent flowmeter. A reactor in which influent flow exceeds effluent flow (i.e., volume accumulation in a reactor used for both storage and disinfection) could also produce V norm > 1.…”
Section: Resultsmentioning
confidence: 99%
“…These limitations may stem from incorrectly estimating reactor geometry (i.e., water level versus volume) or incorrectly estimating how water level changes over time. Deem and Feagin () found that 55% of systems did not verify contact chamber volume and that dimensions of contact chambers in five of 11 systems measured did not match the dimensions used for contact volumes. They also observed that half of systems using tanks or clearwells for disinfection contact did not record tank levels.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, disinfection contact time and its design are likely the least understood part of disinfection, and the design of disinfection contact basins is usually performed using a limited number of resources. Furthermore, contact time can be the largest single source of error in determining pathogen inactivation (Deem & Feagin, ).…”
Section: Introductionmentioning
confidence: 99%
“…The work described in this article was prompted by the findings of an earlier study of disinfection data and practice by the Washington Department of Health (WDOH), which found that eight of the nine systems with a BE above 0.1 were using empirically derived values not verified by a tracer study (Deem & Feagin, ). This group included two utilities with unbaffled chlorine contact tanks that were using an unusually high BE of 0.3.…”
Section: Introductionmentioning
confidence: 99%